A study on the classification of China's provincial carbon emissions trading policy instruments: Taking Fujian province as an example - Gang Ding; Yulu Deng; Songsen Lin (Energy Reports, 2019)
In order to reduce greenhouse gas emissions, China's provinces have issued a series of carbon emission trading policies in recent years. As China's first ecological civilization demonstration zone, Fujian Province has also promulgated an array of carbon emission trading policies. Therefore, deeply analyzing the classification of carbon emission trading policies in Fujian Province is of great reference value for other regions to formulate carbon emission trading policies. This paper first introduces the textual formulation of the carbon emission trading policies in Fujian Province, and subdivides the relevant policies into 17 types of policy instruments as per the classification criteria of mandatory, hybrid, and voluntary. Besides, it also classifies and codes the instruments involved in the Fujian provincial carbon emission trading policies using social network analysis method, with a total of 107 social network actors obtained. On this basis, the differences in the composition of various policy instruments are to be compared and analyzed. The Results show that the proportions of mandatory policy instruments, hybrid policy instruments, and voluntary policy instruments are 54.20%, 36.45%, and 9.35%, respectively. The policy instruments used by the Fujian provincial government are dominated by mandatory and hybrid policy instruments, and the voluntary policy instruments account for a relatively low proportion. Currently, what the Fujian government's carbon emissions trading policies focus on is to improve the supervision and accountability mechanism so as to form a complete carbon emission trading supervision and management system. In the process of building a carbon emissions trading market, the government of Fujian Province should strengthen policy support for talent cultivation, carbon credit evaluation system construction, and policies support for projects in finance, and reinforce the construction of voluntary certification emission reduction mechanism in a timely manner, with a view to encouraging the participation of social forces in the construction of the carbon emissions trading market.
Keywords: 330; Carbon emission permit; Carbon emissions trading; Policy instruments; Social network analysis